The Effect Of Company Size And Profitability On Company Value, With Dividend Policy as Mediating - Widodo, Moch. Wahyu; Maharani, Rieska; Makaryanawati (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2025)
Research Aim: This study aims to analyze the factors that influence firm value in non-consumer cyclical industry sectors. Approach: The study employs a descriptive quantitative approach using Partial Least Squares (PLS) analysis with SmartPLS software. Secondary data were obtained from financial reports of companies in the non-consumer cyclical sector listed on the Indonesia Stock Exchange (IDX). The tested variables include profitability, liquidity, leverage, and dividend policy as determinants of firm value. Research Finding: The results show that only profitability has a significant and positive effect on firm value, while liquidity, leverage, and dividend policy do not have a significant influence. This finding emphasizes that investors still prioritize profitability as the main indicator of firm value. Theoretical Contribution/Originality: This study contributes to strengthening the empirical literature on firm value by highlighting the dominance of profitability as a determinant variable in the non-consumer cyclical sector. Practitioner/Policy Implication: The findings provide guidance for investors to assess firm value based on financial performance indicators, particularly profitability, when making investment decisions. Research Limitation: This study is limited to the non-consumer cyclical industry sector and does not include other industries that may show different determinant patterns of firm value.